The Effectiveness of a School-Based Education Program on Oral Health in Bandung Resident: A Pilot Study - Cecep Eli Kosasih; Tetti Solehati; Mardiyono Mardiyono; Mamat Lukman (Universitas Aisyah Pringsewu, 2021)
The lack of an organized school dental health policy in Indonesia requires an affordable, easily accessible, and sustainable strategy. Provision of dental and oral health knowledge delivers by a little doctor at the school level can help the implementation of the program that school-age is the time of peer groups. The school-age is in which children begin to learn basic oral hygiene practices and are most vulnerable to dental caries. This study was conducted to assess the effect of little doctor training on the knowledge, attitudes and skills of little doctors, as well as on the skills and patterns of brushing teeth in Bandung Regency, Indonesia. This research used a quasi-experimental design with pretest and posttest. A total of 12 little doctors and 291 school children in grades 4-6 elementary school from four government schools were included in this study. The instrument consisted of a knowledge and attitude questionnaire, an observation sheet, and a checklist sheet. Evaluation of tooth brushing patterns at school was done every month for 3 months. Data analysis using paired t-test. Data before and after training were compared and it was found that there was a significant improvement in the knowledge, attitudes, practices of the little doctors and students (p = 0.005). Skills and practice patterns of brushing teeth of school children increased significantly after the program (p = 0.005). The results of this study indicate that school-based oral health education methods that involve little doctors are effective for improving oral hygiene in elementary school children.Abstrak: Kurangnya kebijakan kesehatan gigi sekolah yang terorganisir di Indonesia membutuhkan strategi yang terjangkau, mudah diakses, dan berkelanjutan. Pembekalan pengetahuan kesehatan gigi dan mulut yang disampaikan oleh dokter kecil di tingkat sekolah dapat membantu pelaksanaan program bahwa usia sekolah adalah masa peer group. Usia sekolah adalah masa dimana anak-anak mulai mempelajari praktik dasar kebersihan mulut dan paling rentan terhadap karies gigi. Penelitian ini dilakukan untuk menilai pengaruh pelatihan dokter cilik terhadap pengetahuan, sikap dan keterampilan dokter cilik, serta terhadap keterampilan dan pola menggosok gigi di Kabupaten Bandung, Indonesia. Penelitian ini menggunakan desain eksperimen semu dengan pretest dan posttest. Sebanyak 12 dokter kecil dan 291 anak sekolah kelas 4-6 sekolah dasar dari empat sekolah negeri diikutsertakan dalam penelitian ini. Instrumen terdiri dari angket pengetahuan dan sikap, lembar observasi, dan lembar checklist. Evaluasi pola menggosok gigi di sekolah dilakukan setiap bulan selama 3 bulan. Analisis data menggunakan uji-t berpasangan. Data sebelum dan sesudah pelatihan dibandingkan dan ditemukan adanya peningkatan yang signifikan pada pengetahuan, sikap, praktik dokter kecil dan siswa (p= 0,005). Keterampilan dan pola praktik menggosok gigi anak sekolah meningkat secara signifikan setelah program (p= 0,005). Hasil penelitian ini menunjukkan bahwa metode pendidikan kesehatan gigi dan mulut berbasis sekolah yang melibatkan dokter kecil efektif untuk meningkatkan kebersihan gigi dan mulut pada anak sekolah dasar.